The impact of cash calls on the stock market (in the case of rights issues & public issues) / Shazilan Dahalan - Dahalan, Shazilan (1992)
In recent years, equity financing can be considered a popular way of financing in comparison to debt financing. There, are several reasons as to why equity financing has become popular lately. In line with the buoyant economy, companies in the midst of expansion are in need of additional financing. Equity financing as oppose to debt financing is cheaper especially now that the interest rate is on up trend. In addition, the response towards cash calls in a buoyant economy is usually overwhelming. This is a cost-effective way of raising funds. With the rapid growth of the local stock market, there is a need to analyses the impact of the heavy# cash calls on the stock market as a whole. Upon completion of the study, it can be determine . whether the KLSE could absorb excessive cash calls in the near future.